Penjatuhan Sanksi Pidana Penjara Tanpa Rehabilitasi Terhadap Penyalahguna Narkotika - Abraham Rodo Suryono; Elfrida Ratnawati (Law, Development and Justice Review, 2022)
The purpose of this paper is to provide an overview of the rehabilitation order for narcotics abusers themselves. Law No. 35 of 2009 on Narcotics clearly stipulates that rehabilitation is mandatory for abusers. In fact, it is still common for court decisions to be made without rehabilitation for defendants who are proven to be abusers; this is as an example such case in Decision No. 1243/Pid.Sus/2022/PN Sby. This research is a normative juridical research with a statutory approach model (statue approach) and uses secondary data which is carried out by means of literature or literature studies. This study discusses the considerations of judges imposing prison sentences without rehabilitation for narcotics abusers for themselves being reviewed based on the principle of legal certainty). The results of the research show that Judge Decision No. 1243/Pid.Sus/2022/PN Sby, it is basically correct in using Article 127 paragraph (1) but it is not quite suitable in terms of imposing sanctions on the defendant for not ordering rehabilitation pursuant to Article 127 paragraph (2) and (3) of the Law on Narcotics. Thus a decision that is not in accordance with applicable regulations shows law enforcement that does not provide justice and legal certainty.